Subpicosecond dynamics in calf-thymus DNA, in the presence of Zn2+ ions: A Raman spectroscopic study. Issue 3 (2009) - Muntean Muntean, Cristina M. Cristina M.; Bratu Bratu, Ioan Ioan; Nalpantidis Nalpantidis, Konstantinos Konstantinos; Purcaru Purcaru, Monica A. P. Monica A. P.
Abstract : In this paper the Raman total half bandwidths of calf-thymus DNA vibrations have been measured as a function of Zn 2+ ions concentration, in the presence of a constant concentration of Na + ions, respectively. The dependencies of the total half bandwidths and of the global relaxation times, on DNA molecular subgroup structure and on Zn 2+ ions concentration, are reported. It is shown that changes in the subpicosecond dynamics of molecular subgroups in ZnDNA complexes can be monitored with Raman spectroscopy. Particularly, the Raman band parameters for the vibrations at 729 cm −1 (dA), 792 cm −1 (dC, dT and 5'-C–O–P–O–C-3' network), 1094 cm −1 (DNA backbone PO2 − symmetric stretching), 1377 cm −1 (dA, dT, dC), 1489 cm −1 (the guanine N-7 and adenine rings) and 1581 cm −1 (dG, dA) of ZnDNA complexes, in the presence of Zn 2+ ions concentrations that varied between 0 and 250 mM, are presented. In our study, the full widths at half-maximum (FWHM) of the bands in calf-thymus DNA complexes are typically in the wavenumber range from 10 to 50 cm −1 . It can be observed that the molecular relaxation processes studied in this work, have a global relaxation time smaller than 0.94 ps and larger than 0.21 ps. The limit values are characterizing the dA and dG residues, respectively (vibrations at 729 cm −1 and 1489 cm −1 ). Binding of Zn 2+ ions to double helical calf-thymus DNA results for some vibrations in smaller global relaxation times and larger bandwidths, respectively, possible as a consequence of the increased interaction of the base moieties with the solvent molecules in unstacked structures. The fastest and the slowest dynamics for different DNA structural subgroups and different Zn 2+ ions concentrations, respectively, have been analyzed. A comparison between different time scales of the vibrational energy transfer processes, characterizing the ZnDNA structural subgroups has been given. We have found that metal ion's type and concentration are modulators for the (sub)picosecond dynamics of calf thymus DNA molecular subgroups.